Comprehension of Words and Expressive Language Abilities in Children with Developmental Language Disorder - Kamandulytė-Merfeldienė, Laura; Makauskienė , Vilma (Special Education, 2022)
The article discusses the features of the vocabulary of children with developmental language disorder. The quantitative analysis of the children’s language corpus and the results of experimental tasks helped to reveal the peculiarities of word comprehension and production. The results of children with developmental language disorder (n=80) and children with typical language development (n=80) have been compared. The study revealed that children with developmental language disorder performed statistically significantly worse on tasks of comprehension and production of nouns and verbs. Difficulties in comprehension and production of words are determined by the rare use of the word in the child’s environment, the length, the structure of the word, and the abundance of words of similar meaning.
Keywords: language disorders; developmental language disorder; delayed language development; expressive language; word comprehension; word production; noun; verb